2005
DOI: 10.1110/ps.051406805
|View full text |Cite
|
Sign up to set email alerts
|

Not all J domains are created equal: Implications for the specificity of Hsp40–Hsp70 interactions

Abstract: Heat shock protein 40s (Hsp40s) and heat shock protein 70s (Hsp70s) form chaperone partnerships that are key components of cellular chaperone networks involved in facilitating the correct folding of a broad range of client proteins. While the Hsp40 family of proteins is highly diverse with multiple forms occurring in any particular cell or compartment, all its members are characterized by a J domain that directs their interaction with a partner Hsp70. Specific Hsp40-Hsp70 chaperone partnerships have been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
245
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(249 citation statements)
references
References 99 publications
(162 reference statements)
4
245
0
Order By: Relevance
“…Analysis of J proteins from species as diverse as bacteria and humans has shown that a highly conserved "HPD" motif in the N terminus is involved in proper function (26,43). A histidine-toglutamine mutation in the motif was originally identified as a heat-sensitive mutant in E. coli and has been studied in other homologs (44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of J proteins from species as diverse as bacteria and humans has shown that a highly conserved "HPD" motif in the N terminus is involved in proper function (26,43). A histidine-toglutamine mutation in the motif was originally identified as a heat-sensitive mutant in E. coli and has been studied in other homologs (44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction cycle of DnaK is regulated by cofactors called J proteins (DnaJ in bacteria, Hsp40 in eukaryotes) and the nucleotide exchange factor (NEF) GrpE (25,26). Bacteria have only one NEF, and GrpE is essential in Msm (13).…”
Section: Significancementioning
confidence: 99%
“…The type III J-domain proteins, to which OWL1 belongs, represent a functionally distinct group from the DNAJ proteins and are very heterogenous. They have been suggested not to act as chaperones and seem not to bind to non-native polypeptides, although they are still able to recruit Hsp70 proteins, as the binding motifs are highly conserved (Walsh et al, 2004;Hennessy et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Jiv90 does not comprise the J domain, an essential determinant for the interaction of J-domain proteins with chaperones of the Hsp70 family (19). Accordingly, the Jiv-mediated activation of the NS2 protease for cis and trans cleavage is most likely occurring independent of chaperones of the Hsp70 family.…”
Section: Discussionmentioning
confidence: 99%